Damage to left anterior temporal cortex predicts impairment of complex syntactic processing: A lesion‐symptom mapping study. Issue 10 (21st April 2012) - Magnusdottir, S.; Fillmore, P.; den Ouden, D.B.; Hjaltason, H.; Rorden, C.; Kjartansson, O.; Bonilha, L.; Fridriksson, J.
<x xml:space="preserve">Abstract</x> Sentence processing problems form a common consequence of left‐hemisphere brain injury, in some patients to such an extent that their pattern of language performance is characterized as "agrammatic". However, the location of left‐hemisphere damage that causes such problems remains controversial. It has been suggested that the critical site for syntactic processing is Broca's area of the frontal cortex or, alternatively, that a more widely distributed network is responsible for syntactic processing. The aim of this study was to identify brain regions that are required for successful sentence processing. Voxel‐based lesion‐symptom mapping (VLSM) was used to identify brain regions where injury predicted impaired sentence processing in 50 native speakers of Icelandic with left‐hemisphere stroke. Sentence processing was assessed by having individuals identify which picture corresponded to a verbally presented sentence. The VLSM analysis revealed that impaired sentence processing was best predicted by damage to a large left‐hemisphere temporo‐parieto‐occipital area. This is likely due to the multimodal nature of the sentence processing task, which involves auditory and visual analysis, as well as lexical and syntactic processing. Specifically impaired processing of noncanonical sentence types, when compared with canonical sentence processing, was associated with damage to the left‐hemisphere anterior superior and middle temporal gyri and the temporal pole. Anterior temporal cortex, therefore, appears to play a crucial role in syntactic processing, and patients with brain damage to this area are more likely to present with receptive agrammatism than patients in which anterior temporal cortex is spared. Hum Brain Mapp 34:2715–2723, 2013. © 2012 Wiley Periodicals, Inc.